Morphological characterization of native piperacea conserved in vegetation house (Research, Society and Development, 2021)
The Piperácea family has several species of economic, medicinal, ornamental and environmental interest. Embrapa Amazônia Oriental has a collection of native piperaceae to ensure the diversity of these species and their use in breeding programs, among other finalities. This work aimed to describe the morphological characteristics of four species of piperacea preserved in a greenhouse: Piper marginatum Jacq., Piper montealegreanum Yunck, Piper peltatum L. and Piper tuberculatum Jacq. The length and width of leaves, peduncle, petiole, reproductive structures, internodes, and plant height were measured. Growth habit, phyllotaxis of leaves, shape of leaves and stem, presence of lenticels and attack of pests and diseases on specimens were also evaluated. The coloring of leaves, stems and ears was documented using the Munsell chart. The data considered the average of the measurements taken from four specimens, per species, for each evaluated organ and compared to information from the literature. The results showed that there were differences in the morphological characteristics of the plants when grown in controlled environments.